2018
DOI: 10.1007/s11356-018-3152-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential of guava leaves for mitigating methane emissions and modulating ruminal fermentation characteristics and nutrient degradability

Abstract: Guava leaves (Psidium guajava, GL), a high-phenolic- and flavonoid-containing plant resource capable of substituting the high-quality forage, may help in mitigating ruminal methane (CH) emission without adverse impact on nutrient degradability if supplemented at an appropriate level. In order to test this hypothesis, rumen fermentation, CH production, and nutrient degradability of GL either solely or as a substitute of berseem hay (Trifolium alexandrinum, BH) were evaluated in a diet containing 50:50 concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These components have many properties, such as anticarcinogenic, anti-inflammatory, antioxidant, and antimicrobial [15]. Many studies have reported that these PSCs enhance rumen fermentation characteristics by reducing methane emission and increasing animal productivity [16][17][18]. For instance, Wall, et al [19] reported that a blend of plant extracts containing cinnamaldehyde, the main bioactive of cinnamon, can increase milk production and dry matter intake in lactating dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…These components have many properties, such as anticarcinogenic, anti-inflammatory, antioxidant, and antimicrobial [15]. Many studies have reported that these PSCs enhance rumen fermentation characteristics by reducing methane emission and increasing animal productivity [16][17][18]. For instance, Wall, et al [19] reported that a blend of plant extracts containing cinnamaldehyde, the main bioactive of cinnamon, can increase milk production and dry matter intake in lactating dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the low quality and quantity of animal feeds are serious problems that limit the productivity of livestock worldwide. The importance of shrubs, trees, and herbs as fodder sources has been suggested because of their nutritional value (when compared with fodder trees, herbs, grasses, and shrubs with relatively higher levels of neutral detergent fiber, minerals, and crude protein) for grazing animals in low-quality grazing areas for long periods of the year [3,4]. Nowadays, nutritional solutions and strategies are being used to resolve these crises by using alternative feed ingredients, such as tropical and subtropical plants in rabbit rations [5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using phytobiotic plants in ensiling form, such as Neolamarckia cadamba and grape pomace, reduced the relative abundance of Methanobrevibacter , particularly Methanobrevibacter curvatus , Ruminococcaceae NK4A214 , Ruminococcaceae UCG-010 , and Christensenellaceae R-7 , while increasing the abundance of Succiniclasticum (Zhang et al 2022 ; Zhou et al 2021 ). The bioactive components of these plants may explain their inhibition effect on methanogenic bacteria; Al-Sagheer et al ( 2018 ) observed a negative linear correlation between CT and CH 4 production in vitro when guava leaves were used instead of berseem hay containing 1.60, 2.40, 3.14, and 3.10 g CT/kg DM. Moreover, it has been reported that phytobiotic additives do not affect methanogens, although CH 4 production decreases (Chen et al 2021 ; Wang et al 2022a ).…”
Section: Influence Of Phytobiotic Additives In Mitigating the Environ...mentioning
confidence: 99%